Improving Learning Achievement by Applying the Pakem Learning Model - Tiara Putri; Imam Tabroni; Eladdadi Mark; Kruger Margarida (Yayasan Adra Karima Hubbi, 2023)
Background. The success of the teaching and learning process in the classroom will be largely determined by the learning strategy, no matter how complete and clear the other components are, if they are not applied through the right strategy, then these components will have no meaning in the process of achieving goals. Purpose. Therefore, every teacher who will teach is required to apply certain methods or strategies in the implementation of his learning Method. While the objectives of this study are: (a) Want to know the increase in student learning achievement after the application of the learning strategy of improving thinking skills, (b) Want to know the effect of student learning achievement after applying the PAKEM learning model. Results. This research uses action research (action research) as much as 2 rounds, each round consists of four stages, namely: design, activities and observations, reflection, and revision. Conclusion. The targets of this study were fourth grade students at SDIT Al Manar Purwakarta. Data obtained in the form of formative test results, observation sheets of teaching and learning activities.